Menuju Sustainability: Apakah Lingkungan, Sosial dan Tata Kelola berdampak pada Kinerja Keuangan? - Intan Novia Astuti; Sisca Mediyanti; Eliana Eliana; Ainul Ridha (Universitas Muhammadiyah Malang, 2022)
This study aims to assess the impact of Sustainability (sustainability) consisting of environmental, social and governance on the company's financial performance as measured by ROA and ROCE. This research uses a quantitative approach to manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. A total of 13 companies were selected using the purposive sampling method, so that 65 sample data were obtained. The analysis method used in this study is a regression analysis of panel data. The results showed that environmental disclosure did not have an effect on ROA but environmental disclosure had a positive but not significant effect on ROCE. Social disclosure has a positive and significant effect on ROA. Social disclosure has no effect on ROCE. Governance disclosure has a positive and significant effect on ROA but governance disclosure has no effect on ROCE. High environmental disclosures will degrade the company's financial performance. Creating good environmental sustainability requires high costs and modern technology that will reduce the company's profits. Increasing corporate social disclosure, the company's financial performance will also increase. Disclosure of good corporate governance will lead to the achievement of good CSR outcomes so that it will contribute to good financial performance.